Malaria Incidence, Growth, and their Relationship among a Cohort of Malawian Children - Divya Hosangadi; Liana R. Andronescu; Patricia Mawindo; Don P. Mathanga; Terrie Taylor; Miriam K. Laufer; Andrea G. Buchwald (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Child growth impairment and Plasmodium falciparum ( P. falciparum ) infection pose substantive public health challenges, particularly in sub-Saharan Africa. There is a paucity of evidence regarding how P. falciparum infection, which causes clinical malaria, relates to child growth in children under 24 months old. To assess the temporal associations between P. falciparum infection and weight-for-age Z score (WAZ), a secondary analysis of a prospective cohort study conducted from 2016 to 2018 in which 86 Malawian children ( n = 649 observations) were followed from birth to 24 months of age was conducted. The incidence of P. falciparum infection was assessed, as well as whether P. falciparum infection was associated with subsequent reductions in WAZ and whether lower WAZ scores were associated with increased risk of subsequent P. falciparum infection. The authors also investigated whether being mildly to moderately underweight (WAZ < –1.0) at birth was associated with a shorter time to the first P. falciparum infection. Plasmodium falciparum infection (symptomatic or clinical malaria), asymptomatic P. falciparum infection, and clinical malaria were identified separately in all analyses. More than 30% of children experienced P. falciparum infection within the first 6 months of life. Being mildly to moderately underweight was associated with a significantly higher incidence of P. falciparum infection in the subsequent 3 months (adjusted incidence rate ratio: 1.25 [1.02–1.52]). Being mildly to moderately underweight at birth was associated with a shorter time to the first asymptomatic P. falciparum infection. The study findings reveal a high burden of P. falciparum infection among children